A Work in Progress: National Opioid Prescription Reductions Across Orthopaedic Subspecialties in a Contemporary Medicare Sample of 5, 026, 911 Claims. (May 2021) - Acuña, Alexander J.; Jella, Tarun K.; Samuel, Linsen T.; Cwalina, Thomas B.; Kim, Todd S.; Kamath, Atul F.
Abstract : Introduction: As the opioid epidemic continues in the United States, efforts by orthopaedic surgeons to reduce opioid prescriptions remain critical. Although previous studies have demonstrated reductions in prescriptions across surgical specialties, there is limited information regarding contemporary trends in opioid prescriptions across orthopaedic subspecialties. Our analysis sought to estimate the frequency and trends of opioid prescriptions among Medicare Part D enrollees. Methods: The Medicare Provider Utilization and Payment Data: Part D Prescriber Public Use Files from Centers of Medicare and Medicare from 2014 to 2018 were analyzed. These data were merged with the National Provider Identifier Registry to identify the subspecialty of providers. Prescriber opioid prescription rate, days per claim, and claims per patient were calculated. Temporal trends were tested using linear regression. Poisson regression was used to calculate annual adjusted incidence rate ratios while controlling for year, surgeon sex, average patient comorbidity risk score, and average patient age. Results: We analyzed 5, 026, 911 opioid claims prescribed to 2, 661, 762 beneficiaries. Among all orthopaedic surgeons, the opioid prescription rate per 100 beneficiaries significantly decreased over the study period from 52.99 (95% CI, 52.6 to 53.37) to 44.50 (44.06 to 44.93) ( P = 0.002). This decrease was observed for each subspecialty (all P values < 0.05). Similar significant reductions were appreciated across cohorts in the number of claims per beneficiary (all P values < 0.05). The opioid prescription rate among all orthopaedic surgeons and each subspecialty decreased significantly over the study period after controlling for various patient and surgeon characteristics (all P values < 0.05). Conclusion: Orthopaedic surgeons across subspecialties have reduced their rates of opioid prescriptions over recent years. Although increased prescription-limiting legislation, alternative methods of pain control, and prescriber reeducation regarding the correct quantity of opioids needed for postoperative pain relief, ongoing research, and efforts are needed to translate these reductions into clinically meaningful changes.